First-Principles Investigation on Electrochemical Performance of Na-Doped LiNi1/3Co1/3Mn1/3O2 - Gao, Yumei; Shen, Kaixiang; Liu, Ping; Liu, Liming; Chi, Feng; Hou, Xianhua; Yang, Wenxin (Frontiers in Physics, 2021)
The cathode material LiNi1/3Co1/3Mn1/3O2 for lithium-ion battery has a better electrochemical property than LiCoO2. In order to improve its electrochemical performance, Na-doped LiNi1/3Co1/3Mn1/3O2 is one of the effective modifications. In this article, based on the density functional theory of the first-principles, the conductivity and the potential energy of the Na-doped LiNi1/3Co1/3Mn1/3O2 are calculated with Materials Studio and Nanodcal, respectively. The calculation results of the band gap, partial density of states, formation energy of intercalation of Li+, electron density difference, and potential energy of electrons show that the new cathode material Li1−xNax Ni1/3Co1/3Mn1/3O2 has a better conductivity when the Na-doping amount is x = 0.05 mol. The 3D and 2D potential maps of Li1−xNaxNi1/3Co1/3Mn1/3O2 can be obtained from Nanodcal. The maps demonstrate that Na-doping can reduce the potential well and increase the removal rate of lithium-ion. The theoretical calculation results match well with experimental results. Our method and analysis can provide some theoretical proposals for the electrochemical performance study of doping. This method can also be applied to the performance study of new optoelectronic devices.